Phase Modulated 61 GHz Backscatter Transponder for FMCW Radar-Based Ranging - Stein, Wadim; Aleksieieva, Anna; Röhr, S.; Vossiek, Martin (8th German Microwave Conference (GeMiC2014), 2014)
Modulated backscatter transponders allow, low complexity, low power identification and ranging if an FMCW radar is used as a reader. Especially in industrial environments, modulation significantly increases ranging robustness by echo mitigation of passive / unmodulated reflectors. The 61 GHz ISM band is favorable for high resolution ranging due to the high available bandwidth. However, backscatter transponder design is challenging at mm-wave frequencies. In this paper, a low complexity mm-wave backscatter transponder design based on a single Schottky diode switch is introduced that allows for cost efficient manufacturing and low power consumption. A 3D full wave simulation of the proposed backscatter layout, comprising a model of the diode package, combined with its SPICE parameters in a co-simulation procedure, enables accurate circuit optimization. A complete prototype was built using planar technology that includes switch, clock generation and battery interface. Experimental results show an operating range of 20 m with a ranging uncertainty well below 25 mm at a 1 ms sweep duration of the FMCW signal. Transponder power consumption is as low as 2.5 mA with a supply voltage of 2 V.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEH.phasem